Sports science and efforts towards sub-two hour Marathon performance - Mundia Mwangi, F.; Enomoto, Y.; Hong, S.; Perumal Shanmugam, S.; Tian, X.; Gitonga Rintaugu, E.; Fuku, N.; Kidokoro, T. (IntechOpen, 2021)
Performance in different athletic activities has continued to improve over time, with some athletes from diverse parts of the world registering new world records from time to time. With stiff competition from athletes from different parts of the world, constant upgrading of sports science based approaches to training and competition are employed to achieve more success. However, some approaches used to improve sports performance may pose ethical concerns and may challenge sports as a concept of celebrating natural human abilities. This book chapter interrogates the factors associated with efforts towards improvement of performance in endurance sports events, with a specific focus on marathon races, and the future implications for training, competition, and the nature of sports. While the interplay between nature and nurture determines the unique psychophysiological responses to training and competition, technological exploits leading to advanced sports products coupled with favourable natural and/or manipulated internal (body) and external environmental conditions will ensure continued improvement in performance. However, there is a need to censor commercial interest as well as safeguard safety and the nature of sports as a medium to celebrate natural human abilities.